2017
DOI: 10.1186/s12933-017-0544-4
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase-4 (DPP-4) inhibition with linagliptin reduces western diet-induced myocardial TRAF3IP2 expression, inflammation and fibrosis in female mice

Abstract: BackgroundDiastolic dysfunction (DD), a hallmark of obesity and primary defect in heart failure with preserved ejection fraction, is a predictor of future cardiovascular events. We previously reported that linagliptin, a dipeptidyl peptidase-4 inhibitor, improved DD in Zucker Obese rats, a genetic model of obesity and hypertension. Here we investigated the cardioprotective effects of linagliptin on development of DD in western diet (WD)-fed mice, a clinically relevant model of overnutrition and activation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 63 publications
4
66
1
Order By: Relevance
“…As described above, linagliptin ameliorated kidney fibrosis (both tubulointerstitial fibrosis and glomerulosclerosis) and albuminuria in a murine model of type 1 diabetes without altering blood glucose levels [64]. This is consistent with studies showing antifibrotic effects of linagliptin in the heart [80][81][82][83], aorta [84] and peritoneum [85] in animal models. The antifibrotic changes in the kidneys occurred together with inhibition of the endothelial-to-mesenchymal transition (EndMT) [64], which is thought to be an important source of kidney fibroblasts [86][87][88][89] that play a key role in renal fibrosis [90].…”
Section: Antifibrotic Effectssupporting
confidence: 80%
“…As described above, linagliptin ameliorated kidney fibrosis (both tubulointerstitial fibrosis and glomerulosclerosis) and albuminuria in a murine model of type 1 diabetes without altering blood glucose levels [64]. This is consistent with studies showing antifibrotic effects of linagliptin in the heart [80][81][82][83], aorta [84] and peritoneum [85] in animal models. The antifibrotic changes in the kidneys occurred together with inhibition of the endothelial-to-mesenchymal transition (EndMT) [64], which is thought to be an important source of kidney fibroblasts [86][87][88][89] that play a key role in renal fibrosis [90].…”
Section: Antifibrotic Effectssupporting
confidence: 80%
“…Previous studies have shown that western diet increases the expression of TRAF3IP2 in mice and male transgenic mice with cardiomyocyte‐specific TRAF3IP2 overexpression develop spontaneous myocardial hypertrophy, fibrosis, and dysfunction where a gender‐dependent effect of TRAF3IP2 is suggested . In addition, dipeptidyl peptidase‐4 inhibition results in simultaneous reduction of TRAF3IP2, proinflammatory cytokine, and growth factor expression, as well as collagen induction in primary cardiac fibroblasts . This phenomenon which reverses diastolic dysfunction through targeting TRAF3IP2 expression and its downstream inflammatory signaling has cardioprotective effects …”
Section: Discussionmentioning
confidence: 88%
“…The incidence of these three mechanical effects is very low, but is associated with very poor prognosis . Previous studies have shown that western diet increases the expression of TRAF3IP2 in mice and male transgenic mice with cardiomyocyte‐specific TRAF3IP2 overexpression develop spontaneous myocardial hypertrophy, fibrosis, and dysfunction where a gender‐dependent effect of TRAF3IP2 is suggested . In addition, dipeptidyl peptidase‐4 inhibition results in simultaneous reduction of TRAF3IP2, proinflammatory cytokine, and growth factor expression, as well as collagen induction in primary cardiac fibroblasts .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations